Analisis Struktur Percakapan Dalam Podcast Deddy Corbuzier Episode Jerome Polin - Haer, Zuriatin; Ela, Ela; Hasbullah, Hasbullah; Ade Riyanto, Andra (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This research aims to analyze the conversational structure in the Close The Door podcast hosted by Deddy Corbuzier, particularly in the episode featuring Jerome Polin, using a pragmatic approach. The study highlights five key components of conversational structure as outlined by Yule (2006): turn-taking, pauses, overlaps (simultaneous speech), backchannels (listener responses), and adjacency pairs. The method employed is qualitative descriptive with the techniques of passive observation and note-taking. Data were collected through direct observation of the podcast episode and analyzed to identify elements of conversational structure that occur naturally in unscripted interaction. The analysis reveals that all five components are present in the episode, illustrating the dynamic nature of everyday conversation. Turn-taking and backchannels were the most prominent, reflecting collaboration and responsiveness between speaker and interlocutor. Pauses and overlaps appeared as expressions of spontaneity and reflection, while adjacency pairs emerged through question-answer patterns and natural responses.